Different temporal bases for body and arm movements in volleyball serve reception - Benerink, N. H.; Bootsma, R. J.; Zaal, F. T. J. M. (Scandinavian Journal of Medicine & Science in Sports, 2015)
In many sports, successfully intercepting a ball requires players to move both their body and their arms. Yet, studies of interception typically focus on one or the other. We performed an analysis of the moments of first foot and arm movements of elite-level volleyball players during serve reception. Video footage of five international matches of the Netherlands men's national volleyball team allowed the systematic coding and analysis of 347 different serve reception events. For each event, we identified the time of serve (TS) and time of contact (TC). Ball flight time (from TS to TC) varied between and within types of serve (power jump serves, n?=?193, and jumping float serves, n?=?154). Correlation analyses revealed that foot movement was initiated with respect to time from TS, while arm movement was initiated with respect to time until TC. These results suggest that whole-body and arm movements rely on different control processes.